Developing networked online learning designs and its effectiveness on the works of students in education: Case studies in Indonesia - Adlia Alfiriani; Punaji Setyosari; Saida Ulfa; Henry Praherdhiono (OmniaScience, 2022)
This study aims to develop a network design to meet the connection and interaction needs of students during the online learning process. The research and development method used in this research is divided into four stages, namely needs analysis, design, formative evaluation and revision. The results of the formative evaluation showed the learning design developed has a validity value of 90 out of a maximum score of 115 with a very valid category. This showed the design has good integrity and is feasible to be applied in online learning in higher education. The design also received a practicality value of 83 from a maximum of 165 in the very practical category, and the students gave a positive perception because they thought that the design could be easily followed in their online learning. The effectiveness test also shows that the network design is very effective for student work in online learning. This is evidenced by the difference in the average score of student work in the group using the learning network design and those using content-based and collaborative design. Furthermore, there were significant differences between those that used the network design and those that used the content-based design. However, there was no significant difference in student work results between the group using the network design and those using collaborative.